ACADEMIC WRITING MODULE DEVELOPMENT FOR ADVANCED CHINESE BIPA STUDENTS - Setyawan Pujiono; Beniati Lestyarini (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to develop an academic module based on High Order Thinking skills (HOTS) for BIPA students from Guandong University Foreign Studies (GDUFS) and Yunan Mincu University (YMU) China. This research is developmental research which adopts the procedures of research and development by Borg and Gall. The data, including qualitative and quantitative, are collected by questionnaire to obtain data about the feasibility of the academic writing module based on higher thinking skills. The data analysis is using qualitative analysis and descriptive statistics. The results of the study is academic writing modules using higher-order thinking skills, consisting of introduction, content, and complement. The results of the validation from BIPA material expert show that the modules developed are categorized as good in terms of material presentation, organizational writing, language, format, and HOTS content. This is shown from the results of the average percentage of material experts of 82.50 which indicates the module is feasible and good to be used in academic writing learning for BIPA Chinese students.